A Bayesian three-parameter logistic model for early- and late-onset DLTs in oncology Phase I studies. Issue 2 (3rd March 2016) - Zheng, Wei; Zhao, Yang; Lu, Yuefeng; Miao, Harry; Liu, Hengchang
ABSTRACT: We introduce a three-parameter logistic model to analyze the dose limiting toxicity (DLT) as a time-to-event endpoint in oncology Phase I trials. In the proposed model, patients are allowed to stay on trial without the constraint of a maximum follow-up time. Our model accommodates late-onset DLT as well as early-onset DLT, by both of which the dose recommendation is informed. A Bayesian approach is used to incorporate prior knowledge of the test treatment into dose recommendation. Simulation examples show that our proposed model has good operating characteristics in assessing the maximum tolerated dose (MTD).